Implementasi Nilai-Nilai Ekonomi Syariah pada Pondok Pesantren Terpadu Daarul Ilmi - Mutiara Pertiwi; Sabrina Ramadhani; Kanaya Oktaviani; Muhammad Zaini El Wahyu (STEBI Global Mulia Cikarang, 2024)
This research aims to explain the influence of the cooperative or canteen of the Daarul Ilmi Integrated Islamic Boarding School on Sharia Economic values ​​and the influence of entrepreneurship based on Islam in accordance with Maqosyid Syariah and economic goals according to Adam Smith. The method used in this research is a qualitative descriptive method. The results of the analysis of the research data show that there is a positive or negative influence between the attitudes of the market community and the boarding school students, and this cooperative has helped a lot with the economy of the Islamic boarding school and the surrounding community, and the students at the Daarul Ilmi Integrated Islamic Boarding School.